An Analysis of Teachers’ Pedagogical Competence in Teaching English: A Case Study at an Islamic School in Lombok: A CASE STUDY AT AN ISLAMIC SCHOOL IN LOMBOK - Damayanti, Dini; Rama Suhandra, Ika; Ariawan, Soni (English Language Teaching for EFL Learners Journal, 2023)
The purpose of this study is to evaluate instructors' pedagogical proficiency in the teaching of English. Three MA NW Aik Bukak, Lombok, English teachers were involved as the subjects in this research. Qualitative research was conducted through observations and interviews to find out the data. Qualitative analysis was also done by categorizing the findings from observation and interview. The interview was used to determine the pedagogical proficiency of teachers in the English teaching at MA NW Aik Bukak, and the observations were utilized to observe the process of teaching and learning English in the classroom. The results of this study demonstrated that teachers’ pedagogical competence was rated as good revealed in the 18 indicators of pedagogical competence. Additionally, the MA NW Aik Bukak teachers' pedagogical proficiency in teaching English was also considered sufficient confirmed from the interview. Researchers advised the teachers to take an attempt to enhance their strategies and competency before and while teaching. They must also employ some engaging techniques in order to increase students' enthusiasm and motivation in learning English.